Market Competition in Public Procurement of North Macedonia (2021–2025): Economic Analysis of Bidders per Tender - Mitevski, Viktor (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2025)
This paper examines market competition in North Macedonian public procurement using a novel dataset of all public contracts from 2021–2025. We focus on the number of offers (bids) per tender as a key indicator of competition, following models inspired by Fazekas and Kocsis (2017). The analysis explores how institutional factors, particularly the use of electronic procurement tools and the choice of procedure type, influence bidder participation. We find that the average tender in North Macedonia attracts only 2–3 bids, and over one-third of procedures have a single bidder, raising market competition concerns. Using regression analysis with the number of offers as the dependent variable, we show that fully open procedures and e-procurement usage are associated with modestly higher competition, whereas negotiated or restricted procedures reduce the number of bidders. The paper provides descriptive insights (e.g., variation by contracting institution type and by goods/services/works procurement) and discusses implications for public expenditure effectiveness. Our results underscore the importance of transparent, open, and digitalized tendering processes in increasing competition and improving the efficiency of public spending.
Keywords: Public procurement; Competition; Number of bids; E-procurement; North Macedonia